Capital Market Development and Agricultural Sector Output in Nigeria - Edafe, EMUVEYAN, Anthony; EGUNGWU, Ikenna; NDUKA, Joseph (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The capital market is a segment of the financial system that creates the framework and mechanism for harnessing, generating, managing and channeling funds into capital intensive production-oriented long-term projects and business ventures to support the productive sector. In developing economies as Nigeria, the capital market has been fraught with smallness of size, liquidity issues, low trading activities, poor infrastructural facilities, stringent operational requirements to smaller companies and low level of public awareness that culminate to hamper market efficiency. Financial market development theories suppose that the capital market should prop up and drive the productivity and growth of the economy. This study investigated the effect of capital market development indicators on the agricultural sector output in Nigeria. Four capital market development indicators (market capitalization, turnover ratio, all share index and new issues) are the independent variables while real sector output from agriculture is the dependent variable. The data were obtained from Central Bank of Nigeria (CBN) Statistical Bulletin and CBN Annual Report and Accounts. The Auto-regressive Distributive Lag (ARDL) technique was used for model estimation since the Unit roots confirmed the presence of both level I(0) and first difference I(1) stationarity among the variables. The results showed that Capital market development indicators have significant long and short run effect on agricultural sector output in Nigeria; but no causal relationship between capital market development and agricultural sector output. It is recommended that the regulatory authorities and government should encourage the private sector by making policies that will further boost private sector participation in Nigeria.